The Role of Nurses in Enhancing Medication Adherence and Patient Outcomes in Hypertension Management - Ruswati, Ruswati (Institute of Accounting Research and Novation (IARN), 2024)
This research investigates the pivotal role of nurses in enhancing patient compliance with drug therapy among hypertension patients. Hypertension, a prevalent chronic condition globally, requires effective management through consistent adherence to prescribed medications. Despite advancements in pharmacotherapy, non-compliance remains a significant challenge, leading to suboptimal health outcomes and increased healthcare costs. Nurses play a multifaceted role in promoting medication adherence through patient education, counseling, and ongoing monitoring. Their interventions aim to empower patients, improve health literacy, and address barriers to adherence such as medication side effects and lifestyle factors. This study employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to explore the impact of nursing interventions on medication adherence rates and patient outcomes. Quantitative analysis focuses on medication adherence metrics and clinical outcomes, while qualitative insights delve into patient perspectives and experiences with nursing care. Results underscore the effectiveness of nurse-led interventions in enhancing adherence, achieving better blood pressure control, and fostering patient engagement in hypertension management. Ultimately, this research contributes to advancing nursing roles in chronic disease care and underscores the critical impact of nursing interventions on improving patient compliance and health outcomes in hypertension management.